(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This brief paper reports on a workshop titled, An Exploration of Being-at-Home, Homelessness, and Belonging and the Concept of Existential Migration, presented at the first World Congress for Existential Psychotherapy, held in London, May 2015. This workshop is another in a series of attempts to encourage existential therapists to prioritise their own ’experiential knowing’ over philosophical concepts and psychological theories, in this case about home and belonging. It is an expression of the work I and others have been presenting on the concept of Existential Migration (Madison, 2006; Yates, 2015). One of the outcomes of this research is a reconceptualisation of ’home’ as interaction rather than the usual assumption that home refers to a geographical location, usually one’s origin.